Lantern-shaped 3d–4f high-nuclearity clusters with magnetocaloric effect. Issue 30 (12th July 2017) - Lin, Qingfang; Li, Jing; Dong, Yayu; Zhou, Guangpeng; Song, You; Xu, Yan
Abstract : Two lantern-shaped, high-nuclearity 3d–4f clusters were synthesized by using iminodiacetic acid (IDA) and isonicotinic acid (HIN) as the co-ligand under solvothermal conditions. Magnetic studies show a large magnetocaloric effect (MCE) for the gadolinium analogue. Abstract : Two lantern-shaped, high-nuclearity 3d–4f clusters Ln52 Ni52 (Ln = Gd and Dy) were synthesized by using iminodiacetic acid (H2 IDA) and isonicotinic acid (HIN) as the co-ligand under solvothermal conditions. Magnetic studies show a large magnetocaloric effect (MCE) for the gadolinium analogue.